التعليم الزراعي في خدمة التنمية المستدامة – أي وضع بالنسبة للجزائر؟-: Agricultural education in the service of sustainable development - what is the situation for Algeria? - ثورية الماحي, (Journal of North African Economies, 2025)
The study aims to highlight the pivotal role of education in supporting development in all its stages. The study also exposed the reality of agricultural education in Algeria, which comes from a colonial heritage. The study showed that no clear strategy was taken towards sustainable agricultural education after independence, especially in specialized higher education, and this was evident by studying the reality of agricultural education in the National School of Agricultural Sciences. Our study recommends making education in general and agricultural education in particular an important entry point to serve and embody sustainable development in its three dimensions: economic, social and environmental in order to train specialists and farmers who can change agricultural practices and activities that are unfair to the environment and to ensure their sustainability